Hypotheses and their dynamics in legal argumentation. (1st September 2019) - Moguillansky, Martín O.; Rotolo, Antonino; Simari, Guillermo R.
Highlights: Bridging the theoretical perspectives of argumentation between both, legal and CS domains. Mathematical-logic proposal for a formal modeling of legal interpretations. Formal construction of hypotheses for investigation and fact finding. Modeling the legal argumentation dynamics. Abstract: We investigate some legal interpretation techniques from the viewpoint of the Argentinian jurisprudence. This allows the proposal of a logical framework –from a computer science perspective– for modeling such specific reasoning techniques towards an appropriate construction of legal arguments. Afterwards, we study the usage of assumptions towards construction of hypotheses. This is proposed in the dynamic context of legal procedures, where the referred argumentation framework evolves as part of the investigation instance prior to the trial. We propose belief revision operators to handle such dynamics, preserving a coherent behavior with regards to the legal interpretation used. Abduction is finally proposed to construct systematic hypothesization, with the objective to bring semi-automatic recommendations to push forward the investigation of a legal case.